Fungsi dan Penggunaan Aizuchi oleh Pembelajar Bahasa Jepang Menengah dalam Percakapan Bahasa Jepang (Studi Kasus Mahasiswa Universitas Al-Azhar Indonesia) - Ramadhani, Bembi Mulia; Azzahra, Sarah (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2024)
Aizuchiplays a significant role in Japanese conversations, building harmonious interactions between speakers and listeners. However, understanding the usage and functions of aizuchi among Indonesian learners of the Japanese language still needs to be improved. This research aims to analyze the usage, functions, and types of verbal and non-verbal aizuchi in Japanese conversations by intermediate Japanese language learners at Al-Azhar University Indonesia. Qualitative observation methods were used to examine the usage, functions, and types of aizuchi in face-to-face conversations, utilizing role play as the data collection method. The research findings reveal that learners often utilize aizuchi to confirm what is being said by the speaker. The most used verbal aizuchi is the form known as 「感声的表現」 "kanseitekihyougen" which involves short responses particle form, such as 「うん」"un" (yes) and 「あぁ」"aa" (oh). Additionally, nodding is the most frequently used non-verbal form of aizuchi. This study contributes to expanding the understanding of the usage and types of aizuchi in the context of Japanese conversations among Indonesian learners of the Japanese language. Keywords - Aizuchi, Backchannel, Functions, Japanese Learners.